Produção recombinante e caracterização da endoglucanase IV de Trichoderma harzianum - Corrêa, Rafaela Francini (2014)
The present situation of energy and environmental setting in the world has favored the development of alternative energy sources, and has emerged as an option the use of biofuels, such as bioethanol. Besides ethanol produced from sugarcane, there is the alternative of to use plant biomass to get called second-generation ethanol. In Brazil, the major lignocellulosic material used to produce bioethanol is sugarcane bagasse, and this ethanol is obtained by fermentation of the hydrolyzate of the plant cell wall polysaccharides, this hydrolysis is performed normally by enzymes cellulolytic. Microorganisms, such as fungi of the genus Trichoderma, which are filamentous fungi present in the soil, have a variety of these enzymes that convert cellulose into glucose. In this context, the aim of this study was the recombinant production of Trichoderma harzianum IOC-3844 endoglucanase IV and its biochemical characterization. This Endo IV, which presents high similarity with Endo IV of other Thichoderma species, was expressed using the heterologous expression system of the yeast Pichia pastoris, and after be purified, assays were performed to test their activity. The recombinant enzyme hasn t show sign of degradation in any of the substrates used and can t be confirmed its hydrolytic action. However, the literature has been showed that these enzymes have capacity to increase the breaking of lignocellulose by cellulases (or a mix of them). Based on these data, a test was performed to evaluate the ability of endo IV supplemental activity in the cocktail Acellerase 1500 (Genencor) in the hydrolysis of biomass. In the experiment, copper was added as an electron donor and despite the increase in the hydrolysis of sugarcane bagasse the results showed that copper alone improves the cocktail performance. A circular dichroism analysis was performed and showed that the recombinant Endo IV is correctly coiled. The study showed that the enzyme produced at the laboratory has a high level of expression, but its activity couldn t be detected. The intention now is to perform tests with cocktails that don t contain expansins and isolated enzymes in order to verify that the Endo IV has effect upon them.